The Contributions Allocations And The Village Fund To Improve The Economic Growth Of The Village Community In The District Of Ledo - Blasius Manggu; Sabinus Beni (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Village Allocation Funds and Rural Fund to improve the Community Economic Growth in Sub Ledo Bengkayang. This study Aimed to find out how big a contribution Village Allocation Fund and the Village Fund, in enhancing the economic growth of rural communities as well as obstacles in the face. The collection of data was done by library research, field research such as observation, interviews and document verification. This study uses qualitative analysis of data. Researchers used this approach to get a comprehensive, picture of Village Allocation Fund Contributions, Dana village in District Ledo, Bengkayang. Keywords: Village Allocation Fund, Economic Growth, and Rural